Extended evidence for association between the melanoma inhibitory activity 3 gene and myocardial infarction - Koch, Werner; Schatke, Anna; Wolferstetter, Hannah; Mueller, Jakob C.; Schömig, Albert; Kastrati, Adnan (Thrombosis and Haemostasis, 2011)
In a genome-wide scan, isolated single nucleotide polymorphisms (SNPs), including rs17465637, in the melanoma inhibitory activity 3 gene (MIA3) on chromosome 1 were identified to be associated with coronary artery disease and myocardial infarction (MI). Because the role of common variation at the MIA3 locus has not yet been investigated, the aim of this case-control study was to determine the impact of haplotype-tagging SNPs and haplotypes in the MIA3 region on the risk of MI. In a set of nine haplotype-tagging SNPs, rs17465637, but none of the other SNPs, was associated with MI. After adjustments were made for age, gender, history of arterial hypertension, history of hyper-cholesterolaemia, current cigarette smoking and diabetes mellitus, multiple logistic regression analyses showed an increased risk in the carriers of one or two C alleles [adjusted odds ratio (OR) 1.17, 95% confidence interval (CI) 1.04–1.32, and 1.37, 95% CI 1.08–1.74, respectively]. Nine common haplotypes (frequency >1%) were established across the MIA3 region. Two of the haplotypes were associated with an increased risk of MI: the frequent (48%) TGACCAAAG haplotype and the rare (2%) CGACCAAAG haplotype (adjusted OR 1.102, 95% CI 1.002–1.212, and 1.574, 95% CI 1.077–2.298, respectively). Showing association between rs17465637 and MI, this work was consistent with results from the original detection study and most prior replication studies addressing this issue. In addition to correspond with such isolated evidence of association with MI, the present study identified specific haplotypes capturing the risk-related variation in the entire MIA3 region.
Keywords: Genetic risk; haplotype; melanoma inhibitory activity 3 gene; MIA3; myocardial infarction